(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2022)
Mathematical models of optimization of rock destruction process during well drilling are considered. In most models, the criterion for optimization is the speed of mechanical drilling. According to the authors, this criterion does not allow optimal use of chisels. A method for determining the energy consumption of the process by measuring technological parameters is proposed. Primary converters of load on the chisel, drilling pressure of the drilling mud and other technological parameters are designed and manufactured. Analog signals are converted into digital. The pulsating signals are smoothed mathematically. The optimization criterion is the minimum value of process energy consumption